1995
DOI: 10.1093/dnares/2.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Rat Cellular Nucleic Acid Binding Protein (CNBP) cDNA

Abstract: We cloned and sequenced the cDNAs which code for rat cellular nucleic acid binding protein (CNBP). In-frame insertion/deletion differences were found among the clones at two sites in the open reading frame, suggesting alternative splicing of the message or the presence of multiple genes which code for this protein. The deduced amino acid sequence revealed that one rat CNBP sequence was completely identical to its human counterpart. This striking conservation, together with the fact that homologous genes have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…[31][32][33][34][35] This is consistent with our findings in normal controls, where overall ZNF9 expression is higher in slow type 1 fibers than in fast type 2 fibers and early differentiating myocytes (data not shown). However, the localization of ZNF9 changing from the nuclei in undifferentiated myoblasts to the cytoplasm during differentiation to myotubes and the cytoplasmic localization of ZNF9 in mature human muscle fibers in sarcomeric striations at the Z-disks 36 is unexpected for a transcription factor and suggestive of other functions in mature muscle fibers.…”
Section: Discussionsupporting
confidence: 91%
“…[31][32][33][34][35] This is consistent with our findings in normal controls, where overall ZNF9 expression is higher in slow type 1 fibers than in fast type 2 fibers and early differentiating myocytes (data not shown). However, the localization of ZNF9 changing from the nuclei in undifferentiated myoblasts to the cytoplasm during differentiation to myotubes and the cytoplasmic localization of ZNF9 in mature human muscle fibers in sarcomeric striations at the Z-disks 36 is unexpected for a transcription factor and suggestive of other functions in mature muscle fibers.…”
Section: Discussionsupporting
confidence: 91%
“…It contains seven tandem zinc finger repeats that are composed of 14 same amino acid arrangement of Cys-X2 -Cys -X4 -His-X4 -Cys (Armas et al, 2001). So far, CNBP cDNAs have been cloned from human (Rajavashisth et al, 1989), mouse (Warden et al, 1994), rat (Yasuda et al, 1995), chicken (Van Heumen et al, 1997), Xenopus (Flink et al, 1998), Bufo arenarum (Armas et al, 2001), and Danio rerio (Armas et al, 2004), and all of them have been demonstrated to be highly conserved at the amino acid and nucleotide levels.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular nucleic acid binding protein (CNBP), also known as zinc-finger protein 9 (ZNF9), is a zinc-finger protein that binds single-stranded DNA (ssDNA) [Rajavashisth et al, 1989;Michelotti et al, 1995] and RNA [Yasuda et al, 1995;Pellizzoni et al, 1997;Calcaterra et al, 1999;Armas et al, 2004] molecules. CNBP cDNAs have been cloned from mammals [Michelotti et al, 1995;Yasuda et al, 1995;Flink and Morkin, 1995b;Shimizu et al, 2003], chicken [Ruble and Foster, 1998], fish [Armas et al, 2004;Liu and Gui, 2005], and amphibians [Pellizzoni et al, 1997;Armas et al, 2001].…”
mentioning
confidence: 99%